(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background Biosynthesis of nanoparticle mediated pigments has been widely used as an antimicrobial agent against microorganisms. ZnO nanoparticles were synthesized by using pyocyanin from locally isolated Pseudomonas aeruginosa, then characterized and utilized as antimicrobial activity against microorganisms.The goal of this study was to introduce a modified ZnO nanoparticles biosynthesized technique by pyocyanin pigment, which is safer, more efficient, and less expensive. Materials and Methods Luria Bertani broth was inoculated with the organism and kept at room temperature for 120 hours to get the highest production of pigment, chloroform was added to the culture broth at a 2:1 ratio, and a blue layer formed. The blue layer was collected in a dark glass bottle to prevent oxidation and directly used instead of drying the extract. Results The suggested technique is simple to use, requires no special laboratory equipment, and yields a good amount of pure pigment with a maximum spectral peak of 320 nm. The zinc oxid nanoparticles (ZnONPs) were characterized with Uv-VIS revealing a peak with maximum absorbance at 360 nm and Atomic Force Microscopy that indicated the average size 42.74 nm, as well as using FE-SEM and FTIR. Conclusion This study demonstrated a straight forward but efficient approach for biosynthesizing nanopatricles. By employing chloroform containing pyocyanin and simple processes based on biological methods, in which pyocyanin act as reducing agent and stabilizing mediator in the formation of nanostructured, so the nanoparticles were created in their purest form.